Manganese Catalyzed Asymmetric Transfer Hydrogenation of Ketones Using Chiral Oxamide Ligands - Schneekönig, Jacob; Junge, Kathrin; Beller, Matthias (Synlett, 2019)
The asymmetric transfer hydrogenation of ketones using isopropyl alcohol (IPA) as hydrogen donor in the presence of novel manganese catalysts is explored. The selective and active systems are easily generated in situ from [MnBr(CO)5] and inexpensive C2-symmeric bisoxalamide ligands. Under the optimized reaction conditions, the Mn-derived catalyst gave higher enantioselectivity compared with the related ruthenium catalyst.
Keywords: transfer hydrogenation; asymmetric; manganese; chiral ligands; ketones